Penerapan Terapi AIUEO Pada Pasien dengan Stroke untuk Meningkatkan Kemampuan Bicara : Studi Kasus - Atika Oktaviani Djabar; Nova Natalia; Ni Luh Emilia; Janice Sepang (An Idea Health Journal, 2022)
ABSTRACT In the elderly there are many diseases which can attack one of them is a stroke because most of it occur in three quarters of the elderly (65 years old and above) this is happened because in old age the body is no longer productive and experiences physiological deterioration so it is easy to get sick. One of the effects of stroke is impaired speech therefore the implementation of AIUEO therapy is given as one of options to improve speech ability and articulation. The purpose of this research was to obtain an overview of nursing care to the elderly names Mrs. Y who has stroke in the implementation of AIUEO therapy to improve speech ability at Sawidago Village, North Pamona Sub-district, Poso District. Descriptive case study research design, respondent was 1 person, data were collected by using interviews and observation, the instrument used was the FAST assessment format. The data analysis used was data reduction, presentation and conclusion. The intervention given was the implementation of AIUEO therapy. Conclusion of nursing evaluation after conducting nursing actions for 6 meetings the results obtained that the speech ability began to improve. It is hoped that the results of this case study will be useful for community in the future.